Histological evaluation of the effect of low-frequency electric stimulation on healing Achilles tendons in rats - Casagrande,Sharbo Martins (2021)
ABSTRACT Purpose: Histologically evaluate the effects of low frequency electrical stimulation in the treatment of Achilles tendon injuries in rats. Methods: Thirty-four rats underwent Achilles tendon tenotomy and tenorrhaphy. They were randomly allocated in two groups. Half of the sample constituted the experiment group, whose lesions were stimulated with 2 Hz, nonpolarized current and 1 mA, for 14 days. The other animals formed the control group. They were evaluated at 2, 4 and 6 weeks. The histological study was carried out, the collagen density and the wound maturity index were measured. Results: The healing score was higher in the group stimulated at the 6th week (p = 0.018). The density collagen 1 was higher in the group treated at the three times (p = 0.004) and that collagen 3 was higher in the group treated at 6 weeks (p = 0.004). Together, collagen 1 and 3 were higher in the group stimulated at 4 and 6 weeks (p = 0.009, p = 0.004). The maturity index was higher in this group at the three moments (p = 0.017 p = 0.004 and p = 0.009). Conclusion: Low frequency electric stimulation improved healing and increased the quantity of collagen.